Resolving the Origin of the Unidentified TeV Source HESS J1626-490 as a Relic of the Ancient Cosmic-Ray Factory SNR G335.2+0.1 - Tomohiko Oka; Wataru Ishizaki; Masaki Mori; Hidetoshi Sano; Hiromasa Suzuki; Takaaki Tanaka (The Astrophysical Journal)
While decades of observations in the TeV gamma-ray band have revealed more than 200 sources with radio or X-ray counterparts, there remain dozens of unidentified TeV sources, which may provide crucial information of cosmic-ray (CR) accelerators. HESS J1626−490 is an unidentified TeV gamma-ray source but is expected to originate from CRs that escaped from the nearby supernova remnant (SNR) G335.2+0.1 and are interacting with dense interstellar clouds. To test this scenario, we scrutinize the properties of the SNR and search for nonthermal counterparts by analyzing observational data in the radio, X-ray, and GeV gamma-ray bands. From analysis of the H i and ^12 CO ( J  = 1–0) line data, we identify the cloud associated with the SNR and compare the morphologies of the cloud and the gamma-ray emission. The distance and age of the SNR are estimated to be 3.3 ± 0.6 kpc and ∼5 kyr, respectively. From X-ray and GeV gamma-ray data analyses, we find an extended GeV gamma-ray emission overlapping with the SNR and H.E.S.S. source regions but no X-ray emission. The location of the peak of the extended GeV emission changes from near the SNR at ≲1 GeV to the H.E.S.S. source at >10 GeV. We find a spectral hardening at ∼50 GeV, which is consistent with the existence of two components in the gamma-ray emission. We find that a combination of emission from the escaped CRs and the SNR itself can reproduce the observed broadband spectrum, on the assumption that the SNR has accelerated protons to ≳100 TeV in the past.